PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP - Ulfah, Nadia Eza (Departemen Matematika, 2023)
This research compares the problem-solving abilities of students who learn directly with those of students who use the Think Talk Write (TTW) cooperative learning technique. Students in grade VIII of SMPN 12 Padang participated in this study, which employed a non-equivalent control group design. A test for solving mathematical problems served as the study's instrument. Essay questions made up the majority of the test. The goal of data analysis of test results for mathematical problem-solving skills is to determine whether the tested hypothesis is accepted or rejected. According to the findings, pupils who learnt utilizing this learning technique had greater problem-solving abilities than those who learned from teachers directly. This demonstrates how effective this form of cooperative learning is in enhancing students' capacity to solve mathematical issues. As a result, this study offers proof that TTW cooperative learning strategies can help students become better arithmetic problem solvers.Keywords– Mathematical problem-solving, Cooperative learning, Think Talk Write.